Cidade e vegetação: diretrizes para o plano de arborização urbana de São José dos Pinhais-PR - Oliveira, Viviani Cristine de (2018)
The urban trees portrays the most effective form of integration between the city residents and trees. Its benefits are more than just embellishment, they are consequences of the main purpose. The City of São José dos Pinhais-PR has a Street Trees Plan which is the main effective tool to reinforce public administration, however, the city requires a more comprehensive and reformulated plan, taking into account the failures already observed and the necessity of its updates. This research came about due to the concern related to the number of tree supression requests on public roads in the city, many of them without clear justification. With this available information, the goal was to analyze the real plan’s obstacles, providing guidelines able to conduct the elaboration of a new Urban Trees Master Plan, useful to the planning, decision-making and monitoring of the city's trees. It can be concluded whit this dissertation that the urban vegetation needs to be seen as an Environmental Patrimony that fulfills several urban functions essential to the environmental comfort and the physical and mental health of the population. Thus, it is crucial to elaborate a new Plan for SJP that, besides the roads, contemplates other aspects of urban vegetation. The main guidelines of the new plan should be directed towards favoring: the participation of the population; the inclusion of all planning stages in the Urban Trees Plan; respect local specificities; the protection of urban trees remaining or implanted; the valuation and dissemination of environmental services provided by trees; the integrated action of sectors and organs of the Municipal Government of São José dos Pinhais; geoprocessing in planning and decision making; permanent training; the treatment differentiated to the urban environment, seeking to reconcile the green and gray infrastructures.